Changes in chemical form of phosphorus in rice bran during fermentation process as determined by 31P nuclear magnetic resonance spectroscopy. Issue 4 (4th July 2022) - Ooshima, Masatoshi; Yamaguchi, Noriko; Nakanishi, Yoko; Hitomi, Yoshimi; Hiradate, Syuntaro
ABSTRACT: Rice bran contains appreciable amount of phosphorus (P), which can be used as P fertilizers. The efficiency of the P in the rice bran to plants, however, is low, and the fermentation of the rice bran is proposed to improve the P availability for plants. In the present study, 20 kg of rice bran was aerobically fermented by adding 5 kg of rice husk, 0.025 kg of mulch, and 7 L of water and incubating for 35 days with 6 times of stirring, and the changes in the chemical form of P during the fermentation process were investigated by 31 P nuclear magnetic resonance spectroscopy and chemical extraction. Most part (84%) of P in the raw rice bran was myo -inositol-1, 2, 3, 4, 5, 6-hexaphosphate (I6P), which is not available for plants. During the fermentation process, I6P was degraded and transformed into plant-available phosphate anions (orthophosphate). The proportions of the orthophosphate increased to 68% after incubating for 19 days with two times of stirring and 92% after incubating for 35 days with six times of stirring. After the fermentation, the orthophosphate was present as plant available precipitates associated with magnesium and the other monovalent cations. In conclusion, rice bran contains low-available I6P as a major P form, and the fermentation of rice bran accelerates the cleavage of the ester bond of I6P and results in the increased proportion of orthophosphate with high availability to plants.